1999
DOI: 10.1177/153857449903300405
|View full text |Cite
|
Sign up to set email alerts
|

The Popliteal Artery Entrapment Syndrome

Abstract: The purpose of this retrospective study was to evaluate the early and long-term results of vascular reconstruction for popliteal artery entrapment syndrome (PAES). Fourteen patients (18 legs) who underwent surgical treatment for PAES over a 10-year period were included. Seven patients underwent simple myotomy and remained symptom-free for a 5- to 96-month follow-up period. Seven patients underwent myotomy and vein graft: the graft remained patent in four cases, in one case the graft thrombosed and was successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Eleven studies described a median proportion of 11% of limbs (range, 5%-67%) presenting with acute ischemia. 24,26,27,30,33,36,37,41,42,45,49 A median proportion of 38.25% of patients (range, 0%-100%) diagnosed with bilateral PAES was described in 26 studies. In 12 of 30 studies, a median proprtion of 17.5% of limbs (range, 6%-31%) diagnosed with PAES were asymptomatic, whereas this proportion was unclear in seven studies.…”
Section: Patient Demographics and Disease Presentationmentioning
confidence: 96%
See 3 more Smart Citations
“…Eleven studies described a median proportion of 11% of limbs (range, 5%-67%) presenting with acute ischemia. 24,26,27,30,33,36,37,41,42,45,49 A median proportion of 38.25% of patients (range, 0%-100%) diagnosed with bilateral PAES was described in 26 studies. In 12 of 30 studies, a median proprtion of 17.5% of limbs (range, 6%-31%) diagnosed with PAES were asymptomatic, whereas this proportion was unclear in seven studies.…”
Section: Patient Demographics and Disease Presentationmentioning
confidence: 96%
“…Of the 12 studies on PAES containing asymptomatic limbs, surgery was performed for all asymptomatic limbs in eight studies. 27,29,30,40,42,44,45,49 In one series, no surgery was performed in the single described asymptomatic limb. 24 In three studies, it was not possible to determine the proportion of asymptomatic limbs that underwent surgery.…”
Section: Articles Retrieved From Electronic Search N=291mentioning
confidence: 97%
See 2 more Smart Citations
“…18) The patency rate of bypass surgery using vein grafts has been reported to be 57%-65% over a period of 8-10 years. 19,20) Levien, et al 17) reported a case series of 66 limbs that underwent musculotendinous section and 16 limbs that underwent segmental replacement of the occluded popliteal artery with a reversed saphenous vein. All limbs in the solely musculotendinous section group remained with a patent popliteal artery during the follow-up period (median, 3.9 years).…”
Section: Long-term Follow-upmentioning
confidence: 99%